Discretionary Monetary Policy and Socially Efficient Wage Indexation - Waller, C. J.; VanHoose, D. D. (Quarterly Journal of Economics, 1992)
Christopher J. Waller, David D. VanHoose; Discretionary Monetary Policy and Socially Efficient Wage Indexation*, The Quarterly Journal of Economics, Volume 107,